Hey there! I am Using WhatsApp: A Study on the Levels and Patterns of WhatsApp’s Official Usage among Malaysian University Academicians - Ali, Rana Mohsin; Mahomed, Anuar Shah Bali; Yusof, Raja Nerina Raja; Khalid, Haliyana; Afzal, Muhammad Irfan (International Journal of Asian Social Science, 2019)
Today, the highest reach messaging app is WhatsApp, compared to any other channel. Undeniably, having more than a billion users, the top messaging platform’s users are actively exchanging messages, making voice and video calls, sharing documents and pictures, sharing their stories just like other social media apps around the world, free of charge. In WhatsApp usage behavior, Malaysia is considered as digital forerunner because 97% of the Malaysian population uses WhatsApp daily. This research paper provides useful insights about the levels and patterns of WhatsApp usage in Malaysian public and private universities as a means of official communication. The paper discusses the demographic details of 328 respondents and their responses on the patterns and levels of WhatsApp usage at work. The results explained with the help of charts and tables, confirm the high levels of WhatsApp’s official usage among university academicians in Malaysia. The results further explained the patterns, frequency and type of WhatsApp usage in official communication among superiors, subordinates, colleagues etc. It also confirms that most of the staff uses WhatsApp for official communication with colleagues and subordinates but do not prefer much with superiors. The study shows some interesting insights about this medium of communication.